Efecto de producción para control de picudos (Insecta : Coleoptera: Curculionidae), sobre el crecimiento, desarrollo y producción del plátano (2013)
ABSTRACT: In a farm in the municipality of Andes (Antioquia, Colombia), parcels were planted with Dominico Hartón plantain associated with Caturra-type coffee, where weevil damage (Insecta: Coleoptera: Curculionidae) occurred in 100% of the plantain plants, corms of approximately 2 kg were planted under the same association system. From the sowing until harvest, six types of products were applied every two months on these plantations: chemical of the region (Clorpirifos and Carboxin + Thiram), Carbofurán, Beauveria bassiana, and jatropha, pepper, and neem extracts. As a control, corms without any application of chemicals were used. For the statistical analysis, a randomized complete block design was employed with seven treatments, four replicates, and six plants as experimental units. At the moment of harvest no signi cant statistical differences were found among treatments for these variables: height, diameter, number of cluster branches, total weight, and percentages in the extra and second quality plantains. Statistically signi cant differences were found in: weeks from sowing to harvest, with the control and B. bassiana presenting the highest and lowest average times (75.3 and 69.3 weeks, respectively); functional leaves at the time of harvest, in which the chemical of the region and Carbofurán presented the highest and lowest values (approximately 8 and 7); and the percentage in rst quality plantain, in which the control presented the highest value and was statistically different from the extracts.